Literature review on the evolution of management Accounting practices - Tengku Eka Susilawaty; Nurul Izzah Lubis (Institute of Computer Science (IOCS), 2023)
The purpose of this study is to review the evolution of management accounting practices, where MAP is a reference for managers to obtain the right information in terms of decision-making in order to compete with other market organizations. Contingency theory states that there is no ideal approach to organizational leadership that is universally consistent across all organizations and applicable in all circumstances. This theory also examines several factors that help management decide on appropriate management accounting practices, called contingency factors, consisting of external and internal factors. This study uses a narrative technique to review the literature, which consists of a collection and synthesis of previously released studies on the evolution of management accounting practices. Information was acquired from publications by Emerald, Elsevier, Fundacao Escola de Comercio Alvares Penteado, MDPI AG, Routledge, Springer, Taylor and Francis Ltd. that were printed in foreign journals that were listed in the Scopus index. The sample from 2018 to 2023 includes up to 19 articles on the evolution of management accounting practices. Many empirical studies use a quantitative approach where based on factors and considerations it can be concluded that traditional management accounting practices are more widely used than contemporary management accounting practices.